1999
DOI: 10.1017/s0022215100145165
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating oesophageal foreign bodies in the thyroid gland

Abstract: Oesophageal penetration and migration of oesophageal foreign bodies into the thyroid gland is extremely rare with only occasional case reports appearing in the medical literature over the years. This is a retrospective review of four patients who were managed for penetrating oesophageal foreign bodies in the thyroid gland over an 11-year period. The clinical, radiological and intra-operative findings of the four cases are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 7 publications
0
21
0
2
Order By: Relevance
“…The FB began to migrate in the esophagus within 10 h and penetrated the esophageal wall into the surrounding adipose space within about 1 day. The contraction of the cricopharyngeal muscle during swallowing probably played a significant role in this process [11]. Given the barrier roles of the anterior (trachea) and posterior (cervical vertebra) regions of the esophageal wall [11], a FB may penetrate only through the lateral wall of the esophagus toward the level of the right or left thyroid gland (no predilection).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FB began to migrate in the esophagus within 10 h and penetrated the esophageal wall into the surrounding adipose space within about 1 day. The contraction of the cricopharyngeal muscle during swallowing probably played a significant role in this process [11]. Given the barrier roles of the anterior (trachea) and posterior (cervical vertebra) regions of the esophageal wall [11], a FB may penetrate only through the lateral wall of the esophagus toward the level of the right or left thyroid gland (no predilection).…”
Section: Discussionmentioning
confidence: 99%
“…Our patient swallowed a fine, pointed wire. The nature of the FB may facilitate transmural esophageal penetration and subsequent migration to the level of the thyroid gland [11]. Al-Sebeih et al [17] suggested that the more horizontally oriented and sharper the FB is, the higher the risk of penetration.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6] The mechanism of migration is thought to be due to movements of muscles of neck and viscera during voluntary or involuntary movements. [7] In this case though Direct laryngoscopy, and Eosophagoscopy were negative and radiography is positive, as there is no involvement of deep vessels, [8] penetration of thyroid gland [9] and no evidence of injury to deeper structures, is against the possibility of migration of foreign body.…”
Section: Discussionmentioning
confidence: 61%
“…These include the orientation and pointed shape of the fish bone[4], contraction of the cricopharyngeus muscle during swallowing[9] or neck muscles during neck movement, and local inflammation of the esophageal or pharyngeal wall and direct pressure necrosis[10]. In a Singaporean series, there were 24 cases of migrating FBs, and they concluded that all of the migrated FBs were linear, sharp fish bones with horizontal orientation were more likely to migrate extraluminally to the path of least resistance[4].…”
Section: Discussionmentioning
confidence: 99%